Human Resources and Village Financial Management: Survey Research in the Bulo-Bulo Village, Jeneponto Regency - Maksud Hakim (Enrichment : Journal of Management, 2021)
This research was conducted in every Village Head Office located in the Bulo-Bulo Village, Jeneponto Regency. The phenomenon that occurs is that the quality of human resources is still low and there is still a lack of openness or transparency, as a result, village financial management has not shown maximum results. This study aims to determine how much influence the Quality of Human Resources and Transparency have on Village Financial Management in each Village Head Office located in the Bulo-Bulo Village, Jeneponto Regency. The method used in this research is descriptive analysis and verification. The unit of analysis used in this study was the village head in each Village Head Office in the Bulo-Bulo Village, Jeneponto Regency, with 16 respondents. The data analysis method used is Structural Equation Modeling (SEM) through Partial Least Square (PLS) approach using SmartPLS 3.3.3 software. The results of this study indicate that (1) Quality of Human Resources has a significant positive effect on Village Financial Management with a contribution of 49,4%, (2) Transparency has a significant positive effect on Village Financial Management by 30%.